The mystical Exodus in Jungian perspective: transforming trauma and the wellsprings of renewal - Fershtman, Carolyn Shoshana (Routledge, 2021)
The beloved, knocking -- Renewing Jewish mysticism -- Judaism and psychology -- Exile -- Women, copper mirrors, and awakening from the trance of exile -- Moses and awakening the spiritual fire -- Shattered vessels, scattered seeds -- Serach bat Asher and healing the ruptured bridge to collective memory -- Joseph -- light out of darkness -- Lilith, the dark feminine, and the redemptive power of grief -- The watery initiation and learning to trust the ground of being -- The fiery initiation and moving.